A Simple Competitive Model with Production and Storage - Scheinkman, Jose A.; Schechtman, Jack (Review of Economic Studies, 1983)
We study a rational expectations partial equilibrium model of a market for a single storable commodity whose output each period is a function of previous period effort on production and a realization of a shock that affects equally all producers. The final demand is non-random and depends only on each period's price. Risk-neutral producers make production and storage decisions based on forecasts of future price distributions. Existence of equilibrium is proved, and for the case of i.i.d. shocks several comparative statics results are established as well as the existence and stability of a unique stationary distribution.